Perspektif Santri dan Alumni Ma’had Al-Zaytun Terhadap Program Ekonomi Biru Yang Berkelanjutan: Studi Diskursus Teun Adrianus Van Dijk - Rodhiah, Ismi; Sulistyani, Anjar; Abdurrazaq, Muhammad N. (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
The implementation of the blue economy concept as a sustainable development strategy extends not only to the industrial sector but also to Islamic education. Ma’had Al-Zaytun has become one of the pioneers by transforming the ideological ideas of Syaykh Al-Zaytun about the blue economy into a concrete program called “Samudra Biru”, a shipbuilding and marine training project for students. This research aims to examine how the discourse is constructed and received by students and alumni, and how their perspectives are shaped in the context of Islamic education and spirituality. This study uses a descriptive qualitative method with the Critical Discourse Analysis (CDA) approach of T.A. Van Dijk and Joel M. Charon's Symbolic Interactionism theory. Data were collected through in-depth interviews, participatory observation, and documentation studies involving active students and alumni in the maritime field. The results show that the blue economy program at Ma’had Al-Zaytun is a manifestation of discourse transformed into real action, socially accepted through texts, symbols, experiences, and interactions. The discourse not only instills ideology but also fosters ecological awareness and professionalism. Van Dijk’s analysis highlights the role of discourse in shaping collective ideology, while Charon’s theory reveals that the meaning and values of the blue economy are interpreted as responsibility, sustainability, and worship by students and alumni.